IMPLEMENTASI PENGGUNAAN APLIKASI IPASERTUNTAS SEBAGAI SUMBER BELAJAR SEJARAH BAGI SISWA KELAS XI DI SMAN 1 MUARA KOMAM KABUPATEN PASER KALIMANTAN TIMUR - Rochgiyanti; Fadilatul Khotimah, Octaviona; Prawitasari, Melisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The limited resources for learning history in schools located far from regional library services have presented challenges in the field of education. For example, at SMAN 1 Muara Komam, students rely solely on government-published textbooks provided in the school library, while access to additional historical references remains limited. To address this obstacle, the iPaserTUNTAS digital library application is used as an additional history learning resource. This study aims to examine the implementation of iPaserTUNTAS in 11th-grade history learning and explore its contribution to student learning activities. This study used a qualitative method with a case study approach, conducted at SMAN 1 Muara Komam during the 2025/2026 academic year. Participants included one history teacher and 20 11th-grade students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. Data validity was ensured through triangulation of sources, techniques, and time, while analysis followed the interactive model of Miles and Huberman. The results show that iPaserTUNTAS is integrated into history learning through careful planning, alignment with teaching modules, and structured teacher guidance. This application is used in conjunction with presentations, video displays, and other learning media to enrich students' access to historical information. This implementation also encourages active participation, digital literacy, historical thinking, and collaborative learning among students. In conclusion, iPaserTUNTAS has become an efficient digital learning resource that supports history learning by expanding access to historical references, increasing student engagement, and creating a more meaningful and interactive learning experience.